Article XLIII. Parks and Public Grounds, The Municipal Code of Chicago (1881) § 1690 - (:unkn) unknown (General Publisher, 1881)
Prohibited the carry of firearms or throwing of stones or other missiles within any public park. Prohibited cutting, breaking, or in any way injuring or defacing the trees, shrubs, plants, turf, or any buildings, fences, bridges, or other construction or property within any parks.
--
Keywords: CARRY - CERTAIN PUBLIC PLACES